(untitled) (Global Scientific Review, 2023)
There are several methods that can teach writing skill in English to the beginner learners as well-advanced students. One of the famous deductive and effective method of them is – PPP (presentation, practice and production). PPP- is a technique in teaching is simple way to introduce new topic or vocabulary to students. It will be useful for learning foreign languages in the classroom. It possesses three stages that helps students to learn, understand and practice new vocabulary